KOMPETENSI KOMUNIKASI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU SMK KARTIKA V-I BALIKPAPAN - jurnalpps pps; Harsono Harsono; Indra Prasetyo (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
Competence is a basic characteristic consisting of skill, knowledge and other personal attributes that distinguish someone from performing and not performing and is used as a determining tool to predict the success of improving teacher performance at SMK Kartika V-1 Balikpapan. School principals are needed to bridge teachers in Vocational School Kartika V-1 Balikpapan who have direct and indirect links with foundations, education supervisors, structural schools and school committees. The performance of a teacher can be seen from the work results of quality and quantity achieved in carrying out their duties in accordance with the responsibilities given to him. HR Performance is the work performance (output) both carrying out their work duties in accordance with the responsibilities given to them. Communication of school principals with the structural ranks of schools, foundations, education supervisors, school committees and teachers themselves can improve teacher performance so as to create harmonious and pleasant working relationships in the school environment